Building social capital in a traumatized community with small group art practice - Weinbaum, Michelle A. (Kansas State University, 2012)
Small group creative practice has the potential to set the conditions necessary to develop or strengthen community networks, as a form of social capital, in a disempowered, traumatized community. Traumatized communities require the process of building social capital to begin at an earlier point than in other communities and by addressing the background of trauma first. Case studies of three programs present the opportunity to inform the design of future development work with disempowered, traumatized communities like those of many women in countries engaged in armed conflict. The case studies examined are a government founded shelter for abused women; a localized project to teach agricultural skills; and a project to teach women artistic skills as a therapeutic exercise to build trust levels necessary to increase networks. Social capital provided perspective for examining the bonds between individuals and groups and how they affect individuals’ access to resources. Framed by a literature review, the case studies synthesized literature and first hand experiences and knowledge. A question protocol was used to query the case studies in order to identify best practices. The literature review demonstrated that the most reliable indicators of social capital are trust and association and suggests accepted indicators for each. By querying the case studies, it was determined that best practices for a project designed to build social capital in disempowered, traumatized communities include stipulations on the size of groups, how time is scheduled for informal interaction, identifying indicators of trust, and how conditions for group outcomes were met. This study found that, with an intentional design focus on group outcomes, as well as with attention to other best practices, creative practice is a viable method to increase the levels of trust necessary to set conditions for further development of social capital in the identified communities.
Keywords: Social capital; Trauma; Art therapy; Area Planning and Development (0341)